Results from a COVID-19 Rapid Phone Survey in Sri Lanka - Kim, Yeon Soo; de Silva, Tiloka (World Bank, Washington, DC, 2021)
This brief presents the main findings from a rapid phone survey conducted by the World Bank across eight South Asian countries. The primary aim of the survey was to understand changes in the labor market among different groups. Additional questions were included on households’ ability to meet basic needs, safety nets, and coping mechanisms. In Sri Lanka, the survey was implemented between September and December 2020, and therefore helps assess the short-term impact of the COVID-19 crisis.